Signature Pedagogies: Doctoral-Level Teaching Preparation - Casey A Barrio Minton (Teaching and Supervision in Counseling, 2020)
In response to Baltrinic and Wachter Morris (2020), this article includes a history of teaching preparation in counselor education, exploration regarding current status of doctoral-level teaching preparation in counselor education, and review of literature regarding strategies for preparing doctoral students to teach. Supervision and mentorship emerged as key themes in this relatively new area of preparation. The author explores whether current practice is sufficient to identify these processes as signature pedagogies.
Keywords: signature pedagogies; counselor education; doctoral student; teaching